2005
DOI: 10.1200/jco.2005.09.098
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Refractory Hodgkin's Lymphoma Patients With an Iodine-131–Labeled Murine Anti-CD30 Monoclonal Antibody

Abstract: Treatment with (131)I-Ki-4 is effective but can be associated with severe hematotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(56 citation statements)
references
References 43 publications
1
54
0
1
Order By: Relevance
“…An alternative strategy has been to arm mAbs with radionuclides. Radioimmunotherapy using 90 Y-anti-ferritin and 131 I-anti-CD30 antibodies has resulted in partial (PRs) and CRs in HL (12)(13)(14)(15). Deficiencies with these approaches reflect the lack of tumor specificity of ferritin-targeted antibodies and the small number of CD30-expressing Reed-Sternberg cells in the tumor.…”
mentioning
confidence: 99%
“…An alternative strategy has been to arm mAbs with radionuclides. Radioimmunotherapy using 90 Y-anti-ferritin and 131 I-anti-CD30 antibodies has resulted in partial (PRs) and CRs in HL (12)(13)(14)(15). Deficiencies with these approaches reflect the lack of tumor specificity of ferritin-targeted antibodies and the small number of CD30-expressing Reed-Sternberg cells in the tumor.…”
mentioning
confidence: 99%
“…In patients with HL and NHL, investigators attempted to bind CD30 to the toxin ricin or 131 I. However, the presence of side effects such as decreases in serum albumin, edema, and hypotension with the ricin, or severe hematotoxicity in the case of the Iodine-131-coupled antibody, dampened the enthusiasm for these types of treatments (42)(43)(44). In a seminal phase 1/2 study by Ansell and colleagues (45), it was shown that a fully human anti-CD30 immunoglobulin G1 monoclonal antibody (MDX-060) was well tolerated at concentrations up to 15 mg/kg in a mixed patient population, including patients with HL and ALCL.…”
Section: Cd30 Antibodiesmentioning
confidence: 99%
“…An approach that has been recently investigated is the conjugation of anti-CD30 antibody with a radioisotope, given that HL is typically a radiosensitive tumor [83]. Clinical experience with radioimmunotherapy in HL had previously centered upon polyclonal antiferritin antibodies conjugated to either 131 iodine or 90 yttrium.…”
Section: Radioimmunotherapymentioning
confidence: 99%
“…In the pilot study of anti-CD30 based radioimmunotherapy for relapsed/refractory HL, murine anti-CD30 antibody was conjugated to 131 iodine, as this approach permits dosimetry and biodistribution assessments [83]. The 22 patients were heavily pretreated; most had received radiation and autologous stem cell transplantation, and approximately one-third had relapsed within several months of first-line treatment.…”
Section: Radioimmunotherapymentioning
confidence: 99%